Upaya Preventif Melalui Edukasi tentang Gigitan Ular bagi Pelajar di Daerah Endemik - Rosyantita, Tania Tri; A'yunin, Intan Qurratun; Tri Putri, Geby Harlia; Rahmawati, Yeni; Rosmaliati, Rosmaliati (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Snake envenomation is classified as a medical emergency that can result in significant tissue necrosis and potentially fatal outcomes. The Sembalun Bumbung region, situated in a highland or mountainous area and surrounded by dense forest, is considered a high-risk zone for snakebite incidents. The local population, particularly in Sembalun Bumbung, demonstrates limited knowledge regarding appropriate first aid measures for snakebite cases, thereby necessitating a public health intervention aimed at increasing community awareness, with a specific focus on children. a health education outreach was conducted in a single session at MTs NW Gunung Pangsor, involving 50 participants. Educational content was delivered by subject matter expert through a powerpoint presentation, supplemented by a live demonstration using a real snake. The session lasted approximately 45 minutes and was followed by an interactive question-and-answer segment. To assess the participants comprehension, an oral quiz was administered to 10 individuals selected at random. All participants provided accurate and appropriate responses. Consequently, the educational intervention was deemed effective in improving participants knowledge regarding the identification of venomous and non venomous sankes, as well as evidence based strategies for the prevention and initial management of snakebite envenomation